The Effects of The Problem-Based Learnıng Supported by Experiments in Science Course: Students' Inquiry Learning and Reflective Thinking Skills - Huriye Deniş-Çeliker; Seda Dere (Journal of Science Learning, 2022)
This study aims to investigate the effect of the problem-based learning method supported by experiments on the inquiry learning skills of secondary school students and their reflective thinking skills for problem-solving. This research uses a quasi-experimental design with a pretest-posttest control group. This study consists of 21 students in the experimental group and 22 students in the control group from the sixth grade of a public secondary school in Turkey. The inquiry learning skills and reflective thinking skills scale for problem-solving were used as data collection tools in the research. The Electricity Transmission unit was carried out in the experimental group with problem-based learning scenarios supported by the experiment. Activities based on the science course curriculum were carried out in the control group. SPSS-21 was used to analyze the data. As a result of the study, it was concluded that the post-test scores of the inquiry learning skills scale of the students in the experimental group differed statistically significantly from those of the control group students, and this difference was in favor of the experimental group. No significant difference was found between the experimental and control groups in post-test scores regarding reflective thinking skills for problem-solving.